2017
DOI: 10.1002/ejlt.201600513
|View full text |Cite
|
Sign up to set email alerts
|

Influence of atmospheric pressure argon plasma treatment on the quality of peanut oil

Abstract: The effects of exposure to atmospheric pressure argon plasma on the quality of edible oil were studied. Peanut oil was exposed to the plasma that was generated in voltages ranging from 150–170 V and the variations of peroxide value, iodine value, acid value, and brightness of the resultant products were monitored. Besides, the storage stability of the radiated peanut oil was investigated as well. Plasma treatment did not change the acid value, but reduced the iodine value and increased the peroxide value and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Slightly loose Tight and uniform Grade Bad (0-4) General (5-7) Good (8-10) Journal of Food Processing and Preservation alcohols, ketones, and aldehydes. As a result, POV measurement can be used to assess the degree of oxidative degradation of the product [39]. As shown in Figure 1(c), the POV of AkS at different storage temperatures rose with storage duration, from 0.03 to 0.11 g/100 g at 4 °C, 0.15 g/100 g at 25 °C, and 0.16 g/100 g at 37 °C.…”
Section: Slightly Uniformmentioning
confidence: 95%
See 1 more Smart Citation
“…Slightly loose Tight and uniform Grade Bad (0-4) General (5-7) Good (8-10) Journal of Food Processing and Preservation alcohols, ketones, and aldehydes. As a result, POV measurement can be used to assess the degree of oxidative degradation of the product [39]. As shown in Figure 1(c), the POV of AkS at different storage temperatures rose with storage duration, from 0.03 to 0.11 g/100 g at 4 °C, 0.15 g/100 g at 25 °C, and 0.16 g/100 g at 37 °C.…”
Section: Slightly Uniformmentioning
confidence: 95%
“…The AV of the product represents the degree of lipid breakdown and rancidity during storage. Higher AV values correspond to larger quantities of free fatty acids produced by lipid hydrolysis [39]. Antarctic krill has an excessive amount of fat, and the AkS processing was carried out with heat treatment, which contributed to fat oxidation and expedited the increase in primary oxidation.…”
Section: Av Analysismentioning
confidence: 99%
“…CP studies have shown potential inhibition of fungal growth and degradation of mycotoxins. The study of peanuts, cereals for human and animal consumption, malted barley seeds, maize, hazelnuts, and date palm has shown the potential of CP for fungal inactivation and degradation of several mycotoxins [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. The emerging use of CP for fungi inactivation and mycotoxin degradation will be very useful in ensuring mycotoxin-free globally.…”
Section: Emerging Cp Treatment For Removal Of Mycotoxinmentioning
confidence: 99%
“…The acid value AV represented the level of free fatty acids in oil, which was an indicator of oil rancidity 36 .The variations of the AV of peanut oil were exhibited in Table 1. The results indicated that drying temperatures higher than 50 had a negative effect on the AV of peanut oil compared to the control and low temperature drying groups.…”
Section: Chemical Analysis Of Peanut Oil Extracted From Dried Peanut mentioning
confidence: 99%